Proposição e validação de uma escala de mensuração do nível de integração interfuncional entre marketing, logística e produção - Ferreira, Ana Cristina (2016)
The cross-functional integration corresponds to existence of cooperation between functional areas of an organization. The literature presents an extensive content on the elements present in the dynamics of integration, such as: integration factors, points of contact, formality / informality and impacts. However, there is an absence of theoretical definitions, and field studies, that explain ways to measure element \"level of integration\". Thus, the objective of this work is to develop a scale to measure the level of cross-functional integration, considering the context and the characteristics of integration dynamics between Marketing, Logistics and Production. The study was divided into two phases: qualitative and quantitative. In the qualitative phase, a multicase study was performed. Ten managers from two multinationals from agribusiness sector were interviewed. The instrument for data collection was developed with basis on the literature review and content analysis of the interviews. In the quantitative phase, a survey with 179 participants from all regions of Brazil was performed, using a scale with 52 items to measure the constructs: Integration Factors, Formality, informalities, Conflict, Overlap, Impacts and Integration Level. Through Exploratory/Confirmatory Factor Analysis, and Structural Equation Modeling PLS, a parsimonious model was proposed, with four dimensions and 37 variables. Among the findings, the element overlap, found in the qualitative phase, did not present statistical significance for the level of integration, as well as the formalities. The field results highlighted the importance of the integration factors and informalities for the level of integration, as mentioned in the literature. Conflicts appear to have negative relationship with the level of integration, as expected, but significant in the sense that conflicts can negatively influence the level of integration. Finally, reaffirming the literature, the level of integration provides positive impacts for organizations. For this study, we propose a model with reasonable accuracy to predict the integration level. Due to limited research about scales to measure integration level, this paper becomes relevant, also considering aspects not taken into account in other research. The instrument proposed in this paper provides the assessment of cross-functional integration and can help managers identify relationship problems, possible solutions and their respective impacts.